Taxonomic notes on some species of Campanula, sect. Oreocodon - Zeraatkar, Amin; Nasab, Farzaneh Khajoei (Phytotaxa, 2023)
Based on detailed studies of the protologues, types, herbarium specimens, and comparison with living specimens, Campanula hystricula and C. escalerae are reduced under Asyneuma persicum and Campanula perpusilla, respectively. In this publication, we have provided sufficient morphological evidence for the separation of C. persepolitana and C. perpusilla species. In addition, the morphological descriptions are improved by us. The first photographic documentary on living plants and information about habitat, ecology, phenology, and notes on morphological affinities of C. persepolitana and C. perpusilla, are provided to help them better understand. Distribution maps of the species mentioned are also provided.